Genetic polymorphisms of serotonin transporter and receptor 1A could influence success during embryo implantation and maintaining of pregnancy. - Reyes Palomares, Arturo; Lendínez-Ramírez, Ana María; Pérez-Nevot, Beatriz; Cortés-Rodriguez, Miriam; Martínez, Francisco; Garrido, Nicolás; Ruiz-Galdón, Maximiliano; Reyes-Engel, Armando (Elsevier SCI LTD, 2013)
Objective: To explore whether serotonin-related gene polymorphisms influence clinical outcomes of in vitro fertilization (IVF) treatment in recipients using donated oocytes. Design: Nested case-control study. Setting: University-affiliated infertility clinic. Patient(s): Two hundred forty-five women undergoing IVF treatment with donated oocytes. Intervention(s): None. Main Outcome Measure(s): Genotype and haplotype analysis of the serotonin transporter linked polymorphic region (5-HTTLPR), rs1800532, rs6295, rs6313 and rs3813929, between recipients grouped according to the results of the oocyte donation IVF treatment. Result(s): No differences were found between genotype distribution of the Tryptophan hydroxylase 1 (TPH1), serotonin receptor 2A (5-HT2A) and serotonin receptor 2C (5-HT2C) polymorphisms. Recipients carrying LL genotype for 5-HTTLPR suffered lower clinical pregnancy (CP) rates and higher biochemical pregnancy loss (BPL) events. Lower implantation rates (IR) were found in CC carriers for 5-HT1A.rs6295 who also presented higher BPL rates. A lower incidence of CP was observed for LC haplotypes, corresponding to an increase in BPL rates. Conclusion(s) A strong association was found between early pregnancy loss and recipients carrying the 5 HTTLPR and rs6295 genetic variants. Identifying biological processes involving serotonin and embryo implantation may help to understand the dynamics of the maternal-embryo dialogue.
Keywords: Polimorfismo genético; Serotonina; Embriones humanos; Embarazo; 5-HTTLPR; 5-HT1A; Polymorphism; Biochemical pregnancy loss; Serotonin